Carbon usage in yellow-fleshed Manihot esculenta storage roots shifts from starch biosynthesis to cell wall and raffinose biosynthesis via the myo-inositol pathway - Gutschker, Sindy; Rüscher, David; Rabbi, Ismail Y.; Rosado-Souza, Laise; Pommerrenig, Benjamin; Pauly, Markus; Robertz, Stefan; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; Reinert, Stephan; et al. (Plant Journal, 2024)
Cassava is a crucial staple crop for smallholder farmers in tropical Asia and Sub-Saharan Africa. Although high yield remains the top priority for farmers, the significance of nutritional values has increased in cassava breeding programs. A notable negative correlation between provitamin A and starch accumulation poses a significant challenge for breeding efforts. The negative correlation between starch and carotenoid levels in conventional and genetically modified cassava plants implies the absence of a direct genomic connection between the two traits. The competition among various carbon pathways seems to account for this relationship. In this study, we conducted a thorough analysis of 49 African cassava genotypes with varying levels of starch and provitamin A. Our goal was to identify factors contributing to differential starch accumulation. Considering carotenoid levels as a confounding factor in starch production, we found that yellow- and white-fleshed storage roots did not differ significantly in most measured components of starch or de novo fatty acid biosynthesis. However, genes and metabolites associated with myo-inositol synthesis and cell wall polymer production were substantially enriched in high provitamin A genotypes. These results indicate that yellow-fleshed cultivars, in comparison to their white-fleshed counterparts, direct more carbon toward the synthesis of raffinose and cell wall components. This finding is underlined by a significant rise in cell wall components measured within the 20 most contrasting genotypes for carotenoid levels. Our findings enhance the comprehension of the biosynthesis of starch and carotenoids in the storage roots of cassava.
CRIS-Team Scopus Importer:2024-07-12
Keywords: carotenoid content; cassava; cell wall components; Manihot esculenta; myo-inositol; provitamin A; raffinose; starch content

Effective strategies for isolating DNA from members of Asteraceae with high concentrations of secondary metabolites - Bailey, Dustin W.; Attia, Ziv; Reinert, Stephan; Hulke, Brent S.; Kane, Nolan C. (Biotechniques, 2022)
METHOD SUMMARY A protocol for obtaining high-quality DNA extracted from plant tissue of species known to have interfering secondary metabolites is described.
CRIS-Team WoS Importer:2022-02-18

Identification of heat stress-related genomic regions by genome-wide association study in Solanum tuberosum - Kaier, Alexander; Beck, Selina; Ingold, Markus; Corral García, José María; Reinert, Stephan; Sonnewald, Uwe; Sonnewald, Sophia (Genomics, 2024)
The climate crisis impairs yield and quality of crucial crops like potatoes. We investigated the effects of heat stress on five morpho-physiological parameters in a diverse panel of 178 potato cultivars under glasshouse conditions. Overall, heat stress increased shoot elongation and green fresh weight, but reduced tuber yield, starch content and harvest index. Genomic information was obtained from 258 tetraploid and three diploid cultivars by a genotyping-by-sequencing approach using methylation-sensitive restriction enzymes. This resulted in an enrichment of sequences in gene-rich regions. Population structure analyses using genetic distances and hierarchical clustering revealed strong kinship but weak overall population structure cultivars. A genome-wide association study (GWAS) was conducted with a subset of 20 K stringently filtered SNPs to identify quantitative trait loci (QTL) linked to heat tolerance. We identified 67 QTL and established haploblock boundaries to narrow down the number of candidate genes. Additionally, GO-enrichment analyses provided insights into gene functions. Heritability and genomic prediction were conducted to assess the usability of the collected data for selecting breeding material. The detected QTL might be exploited in marker-assisted selection to develop heat-resilient potato cultivars.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Abiotic stress; GBS; GWAS; Mixed models; Potato; Tetraploid

Quantitative genetics of pleiotropy and its potential for plant sciences - Reinert, Stephan (Journal of Plant Physiology, 2022)
CRIS-Team Scopus Importer:2022-09-09
Keywords: Multivariate; Pleiotropy; Quantitative genetics; Univariate